A photo-responsive micro/nanomembrane for smart separation and self-cleaning - Li, Zhengtao (2023)
Inspired by the micro/nanostructures of a leaf surface, a smart photo-responsive zinc oxide (ZnO) nanorod-modified polysulfone (PSF) nano-fibrous membrane was successfully fabricated using a combination of electrospinning and hydrothermal reactions in this research. Via a hydrothermal reaction, ZnO nanorods can be grown easily on the electrospun PSF nanofibers to form a hierarchical micro-/nano-structure with a large specific surface area. Importantly, due to the photo-sensitivity of ZnO nanorods, the membrane became hydrophilic and performed efficient oil–water separation under ultraviolet (UV) irradiation. Moreover, this membrane demonstrated self-cleaning properties which promoted the degradation of foulants and contaminants under UV irradiation. This novel membrane is a good candidate for smart separation applications.